Z historii opieki. Szpitale i zakłady zakonne dla dzieci w tradycji polskiej = From the history of caregiving. Monastic hospitals and care institutions for children in Polish tradition - Bartkowiak, Edyta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the best experience of religious orders in the history of child care. In Polish tradition the origins of foster care are associated with the formation of the first monastic hospitals - almshouses for children and later monastic orphanages. The history of the Catholic Church is also connected with the origins of children?s homes, the archetypes of contemporary kindergartens. Female orders also contributed to the formation of other forms of care, including nurseries, or once fashionable shelter houses. This analysis presents the activity of nuns in each of these areas and the changes that have occurred in the major forms of child care over time.
Keywords: opieka nad dzieckiem; formy opieki nad dzieckiem; Szpital; przytułek; sierociniec; ochronka dla dzieci; przedszkole; żłobek; pogotowie opiekuńcze; siostry zakonne; zgromadzenie zakonne; child care; forms of child care; hospital; almshouse; orphanage; children`s homes; kindergarten; nursery; shelter houses; nuns; religious congregation